Construct Validity of the Maslach Burnout Inventory in Mental Health Workers: Differentiation from Traumatic Stress Disorders - Helmes, Edward (Archives of Business Research, 2015)
The construct of psychological burnout has been in the literature for decades, and has been largely assessed through C. Maslach’s Maslach Burnout Inventory (MBI). Much of the research on the MBI has been on human service and education workers and has stressed the differentiation of groups. Here we summarize the results of two studies with groups of therapists and explore the relative ability of burnout as assessed by the MBI to differentiate stress disorders that are likely to arise in therapists who deal with clients who have been exposed to severe forms of psychological or physical trauma, namely posttraumatic stress disorder and compassion fatigue or secondary traumatic stress disorder (STSD). Study 1 compared 21 workers from sexual assault centres, 47 from women’s refuges, and 21 other counselors and found higher levels of burnout and posttraumatic stress disorder in the sexual assault workers. Study 2 differentiated 19 therapists with posttraumatic stress disorder from secondary traumatic stress disorder in a second group of 51 therapists exposed to many clients with traumatic experiences, and contrasted them with a group of 55 generic mental health workers. Results showed that the groups did not differ in burnout, but the measure of secondary stress disorder did differentiate the two groups with traumatic stress disorders from the generic mental health workers. While the MBI showed some ability to distinguish therapists with symptoms of PTSD from other practitioners, it was less able to discriminate cases of STSD.